Hubungan Aktivitas Fisik dengan Kejadian Sindrom Pramenstruasi pada Mahasiswi Unisba - Reisya Nur Adisty; Arief Budi Yulianti; Annisa Rahmah Furqaani (Bandung Conference Series: Medical Science, 2024)
Abstract. Asian countries have a higher prevalence of premenstrual syndrome compared to western countries. The prevalence rate of premenstrual syndrome in Indonesia according to research conducted in 2020 reached 85% of the female population of reproductive age. One factor in the increase in premenstrual syndrome symptoms is decreased physical activity. This study aims to analyze the relationship between physical activity and the incidence of premenstrual syndrome in female students at Bandung Islamic University. The design used was cross-sectional with 199 respondents. The type of research used was analytical observational. The data collected was primary data using the American Family Physician questionnaire for PMS and using the International Physical Activity Questionnaire for physical activity. The results of the study were carried out after the chi-square test was carried out to find the relationship between physical activity and the incidence of premenstrual syndrome. Based on statistical test results, a probability value of 0.000 < 0.05 was obtained, this means that there is a relationship between physical activity and the incidence of premenstrual syndrome in active undergraduate students at Bandung Islamic University who have experienced menstruation. Lack of physical activity will cause endorphin deficiency in the body which can result in premenstrual syndrome. However, physical activity in the form of exercise can stimulate the release of endorphins and create a feeling of calm when premenstrual syndrome occurs. Abstrak. Negara asia mempunyai prevalensi terjadinya sindrom pramenstruasi yang lebih tinggi dibandingkan dengan negara-negara barat. Tingkat prevalensi sindrom pramenstruasi di Indonesia menurut penelitian yang dilakukan pada tahun 2020 mencapai 85% dari populasi wanita usia reproduksi. Salah satu faktor terjadinya peningkatan gejala sindrom pramenstruasi adalah aktivitas fisik yang menurun. Penelitian ini bertujuan untuk menganalisis hubungan aktivitas fisik dengan kejadian sindrom pramenstruasi pada mahasiswi Universitas Islam Bandung. Desain yang digunakan adalah potong-lintang dengan responden 199. Jenis penelitian yang digunakan adalah observasional analitik. Data yang dikumpulkan merupakan data primer menggunakan kuesioner American family Physician untuk pms dan menggunakan international physical activity questionnaire untuk aktivitas fisik. Hasil penelitian setelah dilakukan uji chi-square untuk mencari hubungan antara aktivitas fisik dengan kejadian sindrom pramenstruasi. Berdasarkan hasil uji secara statistik diperoleh nilai probabilitas sebesar 0,000 < 0,05, hal ini berarti terdapat hubungan antara aktivitas fisik dengan kejadian sindrom pramenstruasi pada mahasiswi aktif program sarjana di Universitas Islam Bandung yang telah mengalami menstruasi. Kurangnya aktivitas fisik akan menyebabkan defisiensi endorfin dalam tubuh yang dapat mengakibatkan sindrom premenstruasi. Namun dengan aktivitas fisik berupa olahraga dapat merangsang hormon endorfin keluar dan menimbulkan perasaan tenang saat sindrom premenstruasi terjadi.